SIMULATION TRAINING IN MEDICAL STUDENT PREPARATION - Oleg V. Zinchenko; Alla A. Muravyeva; Oksana V. Vladimirova (Moscow Polytechnic University, 2016)
Modernization of Health Care in Russia formed new modern approaches in preparing future specialists in medicine. This article outlines new methods of three-stage preparation of students using simulation technics and involving the students in the role of a simulator for modeling different clinical situation cases. The developed method of preparation and improvement of professional skills of medical students allows to study algorithms of first aid in critical cases more deeply, to learn emergency medical manipulations, to be able to evaluate the results of performed manipulations. Elements of this method can be used in different stages of educational process: in development of practical skills in emergency care, in training to render the first aid in traumas and wounds, and in state attestation.